Multi-agent Based Modeling of Container Terminal Operations - Cahyono, Rully Tri (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2021)
The existing research in container terminal operations systems have not yet fully depicted the entire operations processes. Moreover, these past works tend to use centralized static (linear programming-based) modeling methods to model the systems. A more suitable approach in distributed and changing environment of seaports is dynamical multi-agent systems (MAS). The existing methods (centralized and static) result in high terminal operations cost, which is a burden to the terminal operators. This research aims to utilize of MAS-based dynamics methods, which is also expected to cope the current drawbacks of the sequential communication methods. Eight agents that depict entities in the terminal are ship, port captain, terminal manager, stevedore, quay crane, straddle carrier, customs, and truck. The agents interact in the processes of ship arrival sequencing, determination of shipâ€™s service time and container picking. Based on the simulation result, agentsâ€™ behavior is able toÂ depict the real systems, and the current problem of the operations cost can be reduced up to 3% using our proposed methods. The agents tend to maximize profit in the early period and gradually decrease it to attain common agreement. The velocity of utility function attainment is about 2-5%, but because of the descend monotonic function, negotiation agreement is guaranteed to be attained. Moreover, we provide the detail MAS-based dynamical model as well as the proof that the consensus will be attained by the entire agents.